Problematika Penegakan Hukum Kasus Pembunuhan Berencana di Indonesia: Studi Kasus Pembunuhan Berencana Kopi Sianida oleh Jessica Wongso terhadap Mirna Salihin - Siti Rahma Sagala; Atikah Rahmi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to look at the problems of law enforcement in Indonesia in the case of the premeditated murder of Wayan Mirna Salihin. Whether the judge's decision has provided justice that is as fair as possible to the victim and perpetrator, the evidence presented at the trial does not comply with procedures in accordance with the Criminal Code, the emergence of the films Ice Cold Murder, Coffee and Jessica Wongso has made the public less confident in the law in Indonesia. It is necessary to examine the role of the forensic autopsy in uncovering this case, the discovery of cyanide in Mirna's stomach, which is very strong evidence to prove that the cause of Mirna's death was poisoning by her friend Jessica Wongso. Research methods used used in this research is normative legal research, research using a problem approach, namely judicial case study by approaching the Mirna Salihin premeditated murder case, by examining the judge's decision which resulted in Jessica Wongso being convicted, by conducting this research uncovering the irregularities that occurred in This murder case creates a conflict of interest that cannot be resolved. Jessica Kumala Wongso has been convicted of violating Article 340 of the Criminal Code, namely premeditated murder. In the results of the examination, experts said that a complete autopsy must be carried out for human deaths due to poison. The expert concluded that the cause of WAYAN MIRNA SALIHIN's death was cyanide, especially since 0.2 mg/liter of cyanide was found in the stomach. The judge's decision regarding the premeditated murder of Mirna Salihin did not have any valid and strong evidence at all, starting from the testimony of witnesses who did not there was someone who saw Jessica put poison in the coffee that Mirna was drinking, then the expert's testimony in the examination was not perfect, one of which was that the autopsy did not comply with proper procedures, as well as evidence, such as CCTV which was not original and contrary to regulations. KAPOLRI No. 10 of 2009, as well as the defendant's statement that it never occurred to him to kill his own friend.